Angiolymphoid hyperplasia with eosinophilia and Kimura disease overlap, with evidence of diffuse visceral involvement. (22nd November 2018) - Marka, Arthur; Cowdrey, Molly C. E.; Carter, Joi B.; Lansigan, Frederick; Yan, Shaofeng; LeBlanc, Robert E.
Abstract : A relationship between Kimura disease (KD) and angiolymphoid hyperplasia with eosinophilia (ALHE) has been debated. Given substantial clinical and histological overlap, these entities were once considered to represent a disease spectrum; however, they are now widely considered to be nosologically distinct. A diagnosis of either condition is further complicated by resemblance to various malignancies, which must be carefully excluded. Coexistence of ALHE and KD in a patient is extremely rare, with only four cases reported in the English literature. We report what is to our knowledge the first case of ALHE and KD overlap with evidence of diffuse visceral involvement.